Ballistic Trauma: Lessons Learned from Iraq and Afghanistan - Shin, Emily H.; Sabino, Jennifer M.; Nanos, George P., III; Valerio, Ian L. (Seminars in Plastic Surgery, 2015)
Management of upper extremity injuries secondary to ballistic and blast trauma can lead to challenging problems for the reconstructive surgeon. Given the recent conflicts in Iraq and Afghanistan, advancements in combat-casualty care, combined with a high-volume experience in the treatment of ballistic injuries, has led to continued advancements in the treatment of the severely injured upper extremity. There are several lessons learned that are translatable to civilian trauma centers and future conflicts. In this article, the authors provide an overview of the physics of ballistic injuries and principles in the management of such injuries through experience gained from military involvement in Iraq and Afghanistan.
Keywords: ballistic trauma; blast; combat; casualty; upper extremity trauma